2022
DOI: 10.3390/plants11233206
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Drip Irrigation and Nitrogen Fertilization on Soil Microbial Diversity of Spring Maize

Abstract: Given the shortage of water resources and excessive application of nitrogen fertilizers in irrigated areas, we explored the effect of water–nitrogen coupling on soil microbial diversity in maize fields irrigated using shallow buried droppers. A field experiment (split-plot design) was used with irrigation amounts set at 40%, 50%, and 60% of the conventional amount; furthermore, 13 water and nitrogen coupling treatments were designed. The secondary area was the nitrogen application level, corresponding to 50%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The experimental results in this study demonstrated that the increase in water content (WFPS) significantly reduced the fungal Chao1 and Shannon indices (p < 0.01; Table 3), which was consistent with the results observed by McHugh et al [72]. Several precipitation or water management techniques have distinct effects on the fungal alpha diversity index [72,73]. This is because water quality and water management techniques may have an impact on the responses of diverse microbial communities to soil water availability [74].…”
Section: Soil Microbial Communitysupporting
confidence: 91%
“…The experimental results in this study demonstrated that the increase in water content (WFPS) significantly reduced the fungal Chao1 and Shannon indices (p < 0.01; Table 3), which was consistent with the results observed by McHugh et al [72]. Several precipitation or water management techniques have distinct effects on the fungal alpha diversity index [72,73]. This is because water quality and water management techniques may have an impact on the responses of diverse microbial communities to soil water availability [74].…”
Section: Soil Microbial Communitysupporting
confidence: 91%
“…The application of the maximum nitrogen dose reduced the diversity (Figure 1) while increasing the distance between the bacterial communities of the different treatments (Figure 2). Previous studies have also reported the negative influence of nitrogen supply on the diversity of the soil microbial community [53,78,79]. Indeed, the application of nitrogen fertilizers composed of ammonia acidifies the soil [80,81], and the intensity of this acidity increases with the dose of nitrogen applied [82].…”
Section: Influences Of Various Water Regimes and Fertilization Modes ...mentioning
confidence: 97%
“…Other factors, including soil fertilization, also influence the response of the soil microbial community to drought. It is currently known that an optimal application of N fertilizer mitigates the impact of drought on the microbial community of the soil [52,53]; meanwhile, as its excessive application increases in the long term, so does the sensitivity of the microbial community to various environmental stresses [54]. Other studies have reported a significant improvement in microbial biomass and an alteration in the composition of the soil microbial community under suitable N fertilization in drought conditions [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…The application of fertilizer and the growth of corn are conducive to the metabolic activities of soil microorganisms, which in turn act on the growth of maize (Rao et al, 2021). In agro-ecosystems with high nitrogen input, moderately reducing subsequent nitrogen supply should be the priority choice for soil management (Sarula et al, 2022).…”
Section: Soil Nitrogen Metabolic Enzyme Activity and Composition And ...mentioning
confidence: 99%